TANGGUNG JAWAB MUTLAK ( STRICT LIABILITY ) DALAM PENEGAKAN HUKUM PERDATA LINGKUNGAN DI INDONESIA - Risha Riswanti, Ade; A. Martana, Nyoman; Satyayudha Dananjaya, I Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
The principle of Strict Liability in law enforcement of environmental civil law was formulated in Article 88 Act No. 32 in 2009 of Environmental Protection and Management. But the problem is legal application of principle of Strict Liability have not been effective in ensuring compensation for victims of pollution and environmental destruction. This problem will be researched with the descriptive legal research method to produce an argumentation based on the theory as prescript in finishing the problem faced. Acording to the author,law enforcement on civil law system based on Strict Liability should be through without any specific restriction applicability these principle, and there should be a law enforcement particular courage especially the Judge to applying principle of Strict Liability though contrary to the provisions of civil law.
Keywords: Environmental Law, Liability, Civil Law